Trends in Surgical Morbidity and Survival Outcomes for Radical Hysterectomy in West China: An 11-Year Retrospective Cohort Study - Jing, Huining; Yang, Ying; Liu, Yinxia; Zou, Peijun; Li, Zhengyu (Frontiers in Oncology, 2022)
Objectives To vertically analyze the trend of surgical approaches, demographics, surgical morbidity, and long-term survival outcomes of early-stage cervical cancer over the past 11 years and to determine whether there have been any significant changes. Methods A total of 851 patients with consecutive International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IA–IIA cervical cancer diagnosed between January 2008 and June 2018 at a single center in China were included in this retrospective study. Trends in the rate of minimally invasive surgery (MIS), demographics, surgical morbidities, and long-term survival outcomes were determined. We categorized patients into two groups according to their year of operation. The demographics, pathological factors, surgical morbidity, and long-term survival outcomes were compared between these two groups. Results Regarding the surgical approach, there was a significant increase in the rate of laparoscopic radical hysterectomy (LRH) performed over the study period, from 7.8% in 2008 to 72.5% in 2018 (p < 0.0001). The mean age of patients who underwent abdominal radical hysterectomy (ARH) has increased slightly from 2008 to 2018, and those who underwent ARH in the second half of the study period (2014–2018) were significantly older (45.01 vs. 47.50 years; p = 0.001). The most impressive changes over the past 11 years have occurred in the surgical morbidity in both the ARH and LRH groups. The overall surgical morbidity decreased from 29.2% in 2008 to 11.9% in 2018, with an annual rate of 1.57%. The median estimated blood loss volume of the ARH group was 500 ml (range 50–2,000) in the first few years compared to 400 ml (30–2500) in the last few years of the study period (p < 0.0001), which in the LRH group was 350 ml (range 150–800) and 150 ml (range 5–1,000), respectively (p < 0.0001). Similarly, allogeneic blood transfusions and hospital stay have all decreased dramatically over time in both approaches. On the other hand, our study did not reveal any significant statistical changes in long-term survival outcomes over the follow-up period in either group. Conclusions The findings of our study demonstrate that great progress in surgically managed cervical cancer has been made over the last decade in West China. Our retrospective study demonstrated that the year of operation does not appear to influence the long-term survival, but the surgical morbidity impressively decreased over the study period in both the ARH and LRH groups, which reflects that the higher hospital surgical volume for radical hysterectomy (RH) was not associated with lower survival outcomes but related to the reduction of surgical morbidity.